Pengamatan Oncobasidium theobromae secara Makroskopis dan Mikroskopis, serta Gejala Serangan Sebagai penyebab Penyakit Vascular Streak Dieback (VSD) pada Tanaman Kakao di Kabupaten Sigi, Sulawesi Tengah - Sitti Ardianti; Umrah Umrah; Asrul Asrul (Biology Department, Mathematics and natural science, Tadulako University, 2017)
Oncobasidium theobromae are fungi that causes disease Vascular Streak Dieback (VSD) on the cocoa plants which can causes a totaly death, because the mechanism attack which systemic. The purpose of this study was to observe the morphology of O. theobromae macroscopically and microscopically, as well as symptoms of VSD attack on the cacao plants. This research was conducted from March to August 2016 in the Laboratory of Biotechnology Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University (FMIPA UNTAD). The result of macroscopic observation showed that O. theobromae have white mycelium on the early growth, then the color change to cream and texture like cotton. In microscopic observation, it has branched mycelium and irregular septate. VSD attack symptoms characterized with the leaf has necrosis, the former sitting leaf and the leaf base has three dots, twigs become toothless and the ends of twigs become dry.